SURVEI TINGKAT KETERAMPILAN GERAK DASAR RENANG GAYA DADA PADA SISWA KELAS VIII SMPN 1 KARAWANG TIMUR - Muhammad Luthfi Dharmawan; Astri Ayu Irawan; Saepul Ma’mun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the level of breaststroke fundamental movement skills among grade VIII students of SMPN 1 Karawang Timur in the 2025/2026 academic year. A quantitative approach with descriptive survey method and cross-sectional design was employed. The research subjects were 40 students of class VIII-A selected through cluster random sampling. Data were collected via direct observation using a validated rubric assessment sheet (CVI=0.86; Kappa=0.79; α=0.82) encompassing four components: body position, kick technique, arm pull, and breathing technique. Data were analyzed using descriptive statistics with Azwar’s categorization norms. Results indicated a mean total score of 8.68 (SD=2.31) categorized as Poor. Frequency distribution: Very Poor 25.0%, Poor 17.5%, Fair 35.0%, Good 10.0%, Very Good 12.5%. By component, Body Position obtained the highest mean (2.53), followed by Arm Pull (2.22), Kick Technique (2.07), and Breathing Technique lowest (1.92). These findings indicate the need for improvement in the quality and frequency of swimming instruction at school, particularly in the breathing and kick components.